EFEKTIVITAS FLUBENDIAMIDA DALAM PENGENDALIAN ULAT API Setothosea asigna Van Eecke, ULAT KANTUNG Metisa plana Walker, DAN PENGGEREK TANDAN Tirathaba rufivena Walker SERTA PENGARUHNYA TERHADAP AKTIVITAS KUMBANG PENYERBUK Elaeidobius kamerunicus Faust.EFEKTI - Hari Priwiratama; Tjut Ahmad Perdana Rozziansha; Agus Eko Prasetyo (Pusat Penelitian Kelapa Sawit, 2018)
Flubendiamide is a new insecticide that highly selective against Lepidopteran insect pests. A research was conducted to determine the effects of flubendiamide application on the mortality of nettle caterpillar S. asigna, bagworm M. plana, and bunch moth T. rufivena on mature oil palm. In addition, we also investigated the effects of flubendiamide application on the activity of pollinating weevil E. kamerunicus. Flubendiamide was sprayed directly on the affected oil palm canopy or fruit bunches at the application rate of 0, 50, 100, 150, and 200 mL/ha. On the other hand, flubendiamide was sprayed directly on the anthesis male inflorescences at the dose of 150 mL/ha to study for its impacts against the activity of E. kamerunicus. The results showed that the mortality of each pest increased in line with the dose of application. Flubendiamide was effective against the leaf-eating caterpillar at the application rate of 150-200 mL/ha whilst the application of 200 mL/ha flubendiamide was required for controlling the bunch moth. Moreover, the application of flubendiamide had no adverse effects on the activity and the development of E. kamerunicus on male inflorescences.